Developing an active GPS station based on low-cost GPS instrumentation - Subari, Mustafa Din (1997)
Global Positioning System (GPS) is a satellite-based positioning system globally used for position and velocity determination as well as for precise timing. A GPS Active Station is a set-up in which a GPS receiver located on a known station is operated in a continuous manner, collecting data 'transmitted by the GPS satellites. This setup is also known as Continuous Operating Reference Station (CORS). Normally connected in a network of several other CORS, these stations' serve multi applications. A small research has been on going in UTM to establish a GPS active station, based on low-cost GPS instrumentation. The main objective of this project is to acquire and enhance the technology in operating and maintaining of such station. This paper describes the hardware configuration of the proposed station, as well as the necessary software to be developed in ;order for this station to be operated continuously in an automated manner.